Fidelism and Illustration in an Arequipa writing: The legal Declaration of Pedro José de Zuzunaga y Castillo - Calderón Valenzuela, Fernando (2010)
During the eighteenth century, the Bourbon dynasty in Spain promoted a series of educational reforms that allowed an intellectual flourishing in its American territories, the reforms strengthened the government, but also aroused criticism. While some documents written at this time critically described the colonial scenario in order to promote a series of reforms, others fulfilled the function of strengthening Fidelismo in overseas territories. The authorities of the eighteenth century were aware of the power of discourse as a tool for their consolidation and stability in power. The text written by Pedro José de Zuzunaga y Castillo in Arequipa during the uprising of José Gabriel Condorcanqui (Túpac Amaru II) evidences the changes experienced in the American intellectual elites in this period.